VASA protein and gene expression analysis of human non-obstructive azoospermia and normal by immunohistochemistry, immunocytochemistry, and bioinformatics analysis - Amirian, Mehdi; Azizi, Hossein; Karoii, Danial Hashemi; Skutella, Thomas (Scientific reports, 2022)
VASA, also known as DDX4, is a member of the DEAD-box proteins and an RNA binding protein with an ATP-dependent RNA helicase. The VASA gene expression, which is required for human germ cell development, may lead to infertility. Immunocytochemistry and immunohistochemistry were used to examine the expression of VASA protein in the human testis sections of azoospermic patients, in-vitro and in-silico models. Some studies of fertile humans showed VASA expression in the basal and adluminal compartments of seminiferous tubules. Our Immunocytochemistry and immunohistochemistry in infertile humans showed expression of VASA in the luminal compartments of the seminiferous tubule. The immunohistochemical analysis of three human cases with different levels of non-obstructive azoospermia revealed a higher expression of VASA-positive cells. For this purpose, Enrichr and Shiny Gene Ontology databases were used for pathway enrichment analysis and gene ontology. STRING and Cytoscape online evaluation were applied to predict proteins' functional and molecular interactions and performed to recognize the master genes, respectively. According to the obtained results, the main molecular functions of the up-regulated and downregulated genes include the meiotic cell cycle, RNA binding, and differentiation. STRING and Cytoscape analyses presented seven genes, i.e., DDX5, TNP2, DDX3Y, TDRD6, SOHL2, DDX31, and SYCP3, as the hub genes involved in infertility with VASA co-function and protein-protein interaction. Our findings suggest that VASA and its interacting hub proteins could help determine the pathophysiology of germ cell abnormalities and infertility.
Gesehen am 09.02.2023